Exquisitely-preserved, high-definition skin traces in diminutive theropod tracks from the Cretaceous of Korea - Kim, Kyung Soo; Lockley, Martin G.; Lim, Jong Deock; Xing, Lida (Scientific reports, 2019)
Small theropod tracks, ichnogenus Minisauripus , from the Jinju Formation (Cretaceous) of Korea reveal exquisitely preserved skin texture impressions. This is the first report for any dinosaur of skin traces that cover entire footprints, and every footprint in a trackway. Special sedimentological conditions allowed footprint registration without smearing of skin texture patterns which consist of densely-packed, reticulate arrays of small (<0.5 mm) polygons, preserved as both impressions and casts, the latter essentially foot replicas. The skin texture resembles that reported for two Lower Cretaceous avian theropods (birds) from China which had quite different foot morphologies. This is also the oldest report of Minisauripus from Korea predating five reports from the Haman Formation of inferred Albian age. Minisauripus is now known from six Korean and three Chinese localities, all from the Lower Cretaceous. This gives a total sample of ~95 tracks representing ~54 trackways. With >80% of tracks <3.0 cm long, Minisauripus is pivotal in debates over whether small tracks represent small species, as the database suggests, or juveniles of large species.